Comparison of Individual, Clinical, and Paraclinical Factors in the Survivors and Deceased of COVID-19 - Vahid Yousofvand; Farshid Shamsaei; Naser Kamyari; Fatemeh Shahbazi; Narges Kalvandi; Sajjad Amiri Bonyad (Epidemiology and Health System Journal, 2023)
Background and aims: COVID-19 prevention, diagnosis, and treatment require the identification of high-risk variables. Thus, this study compared the personal, clinical, and paraclinical characteristics of deceased and surviving COVID-19 patients. Methods: This cross-sectional descriptive-analytical study was conducted on COVID-19 patients in the University of Medical Sciences Hamadan hospitals from September 2021 to June 2022. A total of 1948 COVID-19 patients were included in the census. Personal, clinical, and paraclinical data were collected from the medical record. Chi-square, independent t-test, and logistic regression were used to analyze the data in SPSS, version 24. Results: Individual, clinical, and paraclinical variables differed significantly between deceased and surviving COVID-19 patients (P<0.05). Age (over 60 years), complications after COVID-19, frequent cardiopulmonary resuscitation (CPR), use of antifungal drugs, oxygen therapy, underlying disease, insulin, diabetes mellitus, hyperlipidemia, angiotensin II receptor blocker, acidosis, cancer, hypertension, antibiotic use, C-reactive protein, creatinine, bilateral lung involvement, and high levels of potassium were the strongest abnormal predictors of death in COVID-19 patients. Conclusion: Identifying the differences between the deceased and the survivors of COVID-19 in terms of individual, clinical, and paraclinical variables and comparing them with each other in terms of these variables can help in the diagnosis, monitoring, risk assessment, treatment, and prevention of COVID-19.